Assessment of three dynamical urban climate downscaling methods: Brussels's future urban heat island under an A1B emission scenario. (3rd June 2013) - Hamdi, R.; Van de, H.; De, R.; Termonia, P.
ABSTRACT A new high‐resolution dynamical downscaling strategy to examine how rural and urban areas respond to change in future climate, is presented. The regional climate simulations have been performed with a new version of the limited‐area model of the ARPEGE‐IFS system running at 4 km resolution coupled with the Town Energy Balance (TEB) scheme. To downscale further the regional climate projections to a urban scale, at 1‐km resolution, a stand‐alone surface scheme is employed in offline mode. We performed downscaling simulations according to three model set‐ups: (1) reference run, where TEB is not activated neither in 4 km simulations nor in 1 km urban simulation, (2) offline run, where TEB is activated only for 1 km urban simulation and (3) inline run, where TEB is activated both for regional and urban simulations. The applicability of this method is demonstrated for Brussels Capital Region, Belgium. For present climate conditions, another set of simulations were performed using European Center for Medium‐Range Weather Forecasts global reanalysis ERA40 data. Results from our simulations indicate that the reference and offline runs have comparable values of daytime and nocturnal urban heat island (UHI) and lower values than the inline run. The inline values are closer to observations. In the future climate, under and A1B emission scenario, the three downscaling methods project a decrease of daytime UHI between −0.24 and −0.20 °C, however, their responses are different for nocturnal UHI: (1) reference run values remains unaltered, (2) for the offline runs, the frequency of present climate weak nocturnal UHI decreases to the benefit of negative UHIs leading to a significant decrease in the nocturnal UHI over the city and (3) for the inline run, nocturnal UHIs stays always positive but the frequency of the strong UHI decreases significantly in the future by 1 °C. The physical explanation is put forth. Copyright © 2013 Royal Meteorological Society